The Effects of Project-Based Learning in Writing on Students’ Autonomy, Students’ Creativity, and Learning Engagement at SMAN 2 Lintau Buo - Delfita Yulianti; Veni Roza; Absharini Kardena; Melyann Melani (Jurnal Ilmiah Global Education, 2026)
This study is investigated the effects of Project Based Learning (PjBL) on students’ writing ability, autonomy, creativity and engagement at SMAN 2 Lintau Buo, West Sumatera, Indonesia. Writing as productive skills, causes challenges for students, particularly in producing structured and meaningful exposition text. The students also showed low levels of autonomy, creativity, and engagement under conventional instruction. Thus, innovative model like PjBL was implemented to enhance both writing skills and non-cognitive abilities. A quasi-experimental design was employed. The instruments included writing test scored with Jacobs’ rubric, autonomy, creativity, and engagement questionnaires, each validated through Aiken’s V and tested for reliability. The prerequisite of data analysis found that the data were not normally distributed (the sig score < 0.05) and not homogeneous (0.002 < 0.05). So, the data cannot be tested by using parametric test. Hence the Mann Whitney test was used to test the hypotheses.The results revealed that PjBL did not yield significant results in improving writing scores compared to the control group. The p-score 0.542 is greater than 0.05. However, PjBL significantly enhanced students’ autonomy (sig. score 0.001 is smaller than the alpha 0.05), creativity (sig. score 0.001 is less than 0.05), and engagement (sig. score 0.000 is less than 0.05). These findings suggest that while PjBL is not sufficient to improve students’ writing ability, it is effective in fostering non-cognitive skills necessarily for meaningful learning. Implication for teaching recommend combining PjBL with scaffolding to strengthen writing ability while maintaining high levels of autonomy, creativity, and engagement.